Odpowiedzi

Najlepsza Odpowiedź!
2009-10-06T22:06:22+02:00
X + y = 22
z + y = 36
x + z = 34

x = 22 - y
z = 36 - y
22 - y + 36 - y = 34

-2y = 34 - 36 - 22
-2y = -24
y = 12

x = 22 - 12 = 20
z = 36 - 12 = 24
5 4 5
2009-10-06T23:19:02+02:00
Spodek x
filizanka y
szklanka z

x + y = 22
z + y = 36
x + z = 34

x = 22 - y
z = 36 - y
22 - y + 36 - y = 34

x = 22 - y
z = 36 - y
-2y = 34 - 36 - 22

x = 22 - y
z = 36 - y
-2y = -24

x = 22 - y
z = 36 - y
y = 12

x = 22 - 12 = 10
z = 36 - 12 = 24
y=12
3 2 3